How to Influence Privacy Behavior Using Cognitive Theory and Respective Determinant Factors - Ioannis Paspatis; Aggeliki Tsohou (Journal of Cybersecurity and Privacy, 2023)
Several studies have shown that the traditional way of learning is not optimal when we aim to improve ICT users’ actual privacy behaviors. In this research, we present a literature review of the theories that are followed in other fields to modify human behavior. Our findings show that cognitive theory and the health belief model present optimistic results. Further, we examined various learning methods, and we concluded that experiential learning is advantageous compared to other methods. In this paper, we aggregate the privacy behavior determinant factors found in the literature and use cognitive theory to synthesize a theoretical framework. The proposed framework can be beneficial to educational policymakers and practitioners in institutions such as public and private schools and universities. Also, our framework provides a fertile ground for more research on experiential privacy learning and privacy behavior enhancement.